Effects of anthocyanin supplementation in diet on glycemic and related cardiovascular biomarkers in patients with type 2 diabetes: a systematic review and meta-analysis of randomized controlled trials - Mao, Ting; Akshit, F. N. U.; Mohan, Maneesha S. (Frontiers in Nutrition, 2023)
Purpose: This study is the first systematic review and meta-analysis on anthocyanins' effects on type 2 diabetes mellitus (T2DM) subjects based on RCTs and the effect on T2DM related cardiovascular disease.Methods: RCTs published in English from five electronic databases were evaluated for glycated hemoglobin (HbA1c), fasting blood glucose (FBG), 2-hour postprandial blood glucose, fasting insulin, model assessment for insulin resistance, triglycerides (TG), total cholesterol (TC), highdensity lipoprotein (HDL) cholesterol, low-density lipoprotein (LDL) cholesterol, systolic blood pressure, and diastolic blood pressure. The quality of the studies was rated (Cochrane Risk of Bias tool) and weighted mean differences were calculated (DerSimonian-Laird model with random effects). Leave-one-out sensitivity, subgroup, and publication bias analyses were conducted. The strength of the evidence was rated according to the GRADE guidelines.Results: Eleven RCTs were analyzed out of the 233 identified studies, with a duration longer than 4 weeks (607 T2DM participants). Our findings indicate that a median dose of 320 mg/day anthocyanins, either from fruit extracts or pure supplements, for a median intervention length of 12 weeks significantly reduced HbA1c (Weighted Mean Difference (WMD) -0.31, p = 0.00), FBG (WMD -0.63, p = 0.00), 2-hour postprandial glucose (WMD -1.60, p = 0.00), TG (WMD -0.45, p = 0.01), and LDL (WMD -0.26 p = 0.02). However, the effects of anthocyanins on fasting insulin, HOMA-IR, TC, HDL cholesterol, systolic blood pressure, and diastolic blood pressure in T2DM patients were not statistically significant. Anthocyanins from fruit extracts or powder exhibited a higher reduction of HbA1c compared to pure anthocyanin supplements.The significant improvements in glycemic parameters and lipid profile, suggest the benefits of anthocyanins, especially from fruit extract or powder, in the management of T2DM, and their ability to delay the onset of lipid disorder related diseases like cardiovascular disease associated with T2DM. The mechanism behind this reduction in glycemic markers could be attributed to the antioxidant and anti-inflammatory activity of anthocyanins. Further research with well-designed RCTs is required to determine the optimal anthocyanins dosage for the treatment of T2DM and to comprehend the consequences.